Immersion Behavior Study of Hydroxyapatite Scaffolds Derived from Bovine Sources In Acidic, Basic, and Neutral Solutions - Widantha, Komang Widhi (Frontier Advances in Applied Science and Engineering, 2024)
This research investigates the effects of particle size and compaction pressure on the dissolution behavior of hydroxyapatite scaffolds synthesized from bovine bone in acidic neutral and basic solutions. Hydroxyapatite was extracted through a process involving cutting, cleaning, boiling, soaking in NaOH, sun drying, grinding into powder and calcination at 800°C. The powder was then sieved into two size fractions (75 and 150 microns) and compacted at pressures of 200, 250, and 300 MPa. The mass and dimensions of the scaffolds were measured to calculate porosity, followed by immersion in the respective solutions for 24 hours to determine dissolution rates. Results indicated that smaller particle sizes and higher compaction pressures resulted in reduced porosity and enhanced structural integrity. The dissolution rates varied significantly with pH levels, exhibiting the highest rates in acidic conditions up to 215.83 mg/cm2 and the lowest in basic solutions up to 11.32 mg/cm2. Additionally, scaffolds with smaller particles and higher compaction pressures demonstrated lower dissolution rates across all pH levels due to lower porosity. In conclusion, both particle size and compaction pressure are critical factors influencing the dissolution behavior of hydroxyapatite scaffolds. These findings have significant implications for the design and optimization of hydroxyapatite-based materials for biomedical applications, where controlled dissolution rates are crucial for performance and longevity.